The Effect of Human Resource Development, Compensation, and Motivation on the Performance of Teachers at SMK Islam Nurul Hayat Depok - Dandi, Zidan Muhamad; Aryata, I Made (STEBIS Bina Mandiri, 2025)
This research aims to determine the influence of human resource (HR) development, compensation and motivation on teacher performance at SMKI Nurul Hayat Depok, both partially and simultaneously. This research uses a quantitative associative method with a population of 42 teachers and a saturated sampling technique. Data analysis includes instrument testing, classical hypothesis testing, multiple linear regression, coefficient of determination, as well as hypothesis testing via the t test and F test. The results of the analysis show that partially, human resource development (X1) has no significant effect on teacher performance, with tcount=2.023 0.05p>0.05 ), so that H0 is accepted and Ha is rejected. However, motivation (X3) has a positive and partially significant effect on teacher performance, with tcount=4.585>ttable=2.024, significance value 0.000 (p